England's Second Domesday and the Expulsion of the English Peasantry - Dimmock, Spencer (Historical Materialism Book Series, 2024)
The world-shaking forced evictions of English peasants during the fifteenth and sixteenth centuries are treated by most historians as largely a 'Tudor myth'. For them, the peasantry disappeared much later through fair means thanks to industrialisation and trade. Centred on close scrutiny of the royal commission of 1517 - 'England's Second Domesday' - this book overturns these accounts. It demonstrates, unequivocally, that capitalism carved fundamental and irreversible breaches into the English countryside between 1400 and 1620. It began, grew and thrived on widespread illegal clearances of rural people and their culture by the English ruling class, long before the British industrial revolution.